Synergistic Effects of Nitrogen and Zinc Foliar Application on Yield and Nutrient Accumulation in Rice at Various Growth Stages - Patcharin Tuiwong; Hui-Kyong Cho; Hatem Rouached; Chanakan Prom-U-Thai (Plants)
The rising interest in foliar nutrient spraying as a strategy to boost crop yields has led to investigations of how such application influences nutrient uptake and accumulation, especially in edible plant parts. Despite its importance, the effects of single versus simultaneous nutrient application on plant absorption, transport, and accumulation have been underexplored. This study addresses this knowledge gap by examining the physiological and molecular responses of rice to foliar application of nitrogen (N) and zinc (Zn) individually and in combination at different growth stages. We assessed how the treatments affect rice grain yield and nutrient accumulation in relation to the expression of Zn transport-related genes. Foliar application of N+Zn+ at the tillering stage resulted in a 62.01% increase in grain yield compared to the control. Additionally, Zn concentrations in brown rice were increased by 26.04% and 34.20% when N0Zn+ and N+Zn+ treatments, respectively, were applied at panicle initiation. Gene expression analysis revealed that the timing and nutrient combination significantly influenced rice productivity and grain Zn concentration. At the tillering stage, the N+Zn+ treatment elevated the expression of Zn transporters such as OsZIP3, OsZIP4, and OsZIP9 in leaves, thereby enhancing grain yield. At panicle initiation, the nutrient treatments influenced a broad range of genes, including OsZIP4, OsZIP9, OsHAM2, OsDUR3, OsAAP1, OsGS1;1, and OsFd-GOGAT, affecting grain Zn and N accumulation. These insights are crucial for developing targeted nutrient management strategies to optimize rice yield and grain nutritional quality for the benefit of consumers.